Prevalence of Mental Health Problems and Associated Factors among the School Students Aged 13-15 Years in Jaffna District, Sri Lanka - R. Surenthirakumaran; S. Kumaran; P. A. D. Coonghe (College of Community Physicians of Sri Lanka, 2021)
Introduction: Mental health problems have a noticeable effect on the academic and non-academic performance of the students. Strength and Difficulties Questionnaire (SDQ) is one of the most widely used instruments for screening behavioural problems in children.   Objectives: To estimate the prevalence of mental health problems, and association of socio-cultural and school related factors on it among the school students aged 13-15 years in Jaffna District.   Methods: A school-based analytical cross-sectional study was conducted among 800 students aged 13-15 years studying at government schools in Jaffna district from June 2016 to November 2017. The Tamil version of validated SDQ was used for this survey. Chi-squared test was performed and odds ratios were calculated. Independent variables with significant influence were entered to the logistic regression analysis, and individual contributions were identified. A p value less than 0.05 was considered as statistically significant and 95% confidence intervals were calculated.   Results: The study sample consisted of 408 (51.0%) boys and 392 (49.0%) girls. It showed 21.5% (n=172) of the students had mental health problems. Boys had significantly (p<0.001) higher mental health problems than girls (26.5% vs. 16.3%). Mean scores for conduct (2.39; SD=1.63), hyperactivity (2.66; SD=1.82), peer (2.24; SD=1.74) subscales were significantly higher among boys, while the significantly higher score was obtained in emotional (3.22; SD=2.07) and pro-social (8.48; SD=1.5) scales among females. Gender, living with both parents, education level of mother and father, supplementation of vitamin A and folic acid, and performance in mathematics had a statistically significant association with the mental health status of the students.   Conclusions & Recommendations: Boys had more mental health problems compared to girls of the same age and several socio-cultural factors associated with it.